Leukotriene receptors (version 2020.3) in the IUPHAR/BPS Guide to Pharmacology Database. (2020) - Bäck, Magnus; Brink, Charles; Chiang, Nan; Dahlén, Sven-Erik; Dent, Gordon; Drazen, Jeffrey; Evans, Jilly F.; Hay, Douglas W. P.; Nakamura, Motonao; Powell, William; Rokach, Joshua; Rovati, G. Enrico; et al.
No abstract available